Cochliomyia hominivorax (Coquerel, 1858) and Phaenicia sericata (Meigen, 1826) parasiting domestic animals in Buenos Aires and vicinities (Diptera, Calliphoridae) - Mariluis, Juan Carlos (1994)
Fil: Mariluis, Juan Carlos. Instituto Nacional de Microbiología Dr. Carlos Malbrán. Departamento de Parasitología. Buenos Aires; Argentina